Comparative evaluation of implant designs: Influence of diameter, length, and taper on stress and strain in the mandibular segment-A three-dimensional finite element analysis - Gowthama Raaj; Pulliappan Manimaran; Chandran Dhinesh Kumar; Duraisamy Sai Sadan; Mathivanan Abirami (Wolters Kluwer Medknow Publications, 2019)
Introduction: Success or failure of dental implants depends on the amount of stress transferred to the surrounding bone. Increased amount of loading to the bone through implant cause failure, whereas decrease in the amount of loading to the bone causes improved success rate of implants. Biomechanical interaction between implant and bone decides the long-term function or prognosis of dental implant system. Aim and Objectives: The aims of this study were to evaluate the influence of implant length and diameter on stress distribution, to understand the stress distribution around bone-implant interface, and to understand the response of bone under axial and non-axial loading conditions. Materials and Methods: Finite element three-dimensional mandibular model was made using cone beam computed tomography of patient with completely edentulous mandible, and in that model five posterior bone segments were selected. NobelReplace Select Tapered implants with diameters and lengths 3.5×10mm, 4.3×10mm, 3.5×11.5mm, and 4.3×11.5mm, respectively were selected and three dimensionally modeled using Creo 2.0 Parametric Pro/E software. Bone and implant models were assembled as 20 models and finite element analysis was performed using ANSYS Workbench v17.0 under axial and non-axial loads. Result: Under axial and non-axial loads, 3.5×10mm implant showed maximum von Mises stress and strain in both cortical and cancellous bone whereas implant with diameter and length 4.3×11.5mm showed minimum von Mises stress and strain in both cortical and cancellous bone. Conclusion: In axial and non-axial loads, amount of stress distribution around implant-bone interface is influenced by diameter and length of implant in cortical and cancellous bone, respectively. Increased diameter of the implant produces the minimum stress in cortical bone. Increased length of the implant produces the minimum stress in cancellous bone.